One‐dimensional nanomaterial supported metal single‐atom electrocatalysts: Synthesis, characterization, and applications - Haoyue Zhao (Wiley-VCH, 2021)
Abstract Metal single‐atom catalysts (MSACs) have attracted considerable attention in the field of electrocatalysis due to their maximized atomic utilization, high activity, and superior selectivity. As a class of supported catalyst, the type of support material plays a key role in stabilizing metal single atoms (MSAs) and improving the overall catalytic performance. One‐dimensional (1D) nanomaterials are regarded as ideal supports for MSACs owing to many of their unique advantages, such as controllable surface physicochemical properties, large specific surface area, efficient electron transfer pathway, and great flexibility in element selection. Therefore, recently developed MSACs supported by various types of 1D nanostructured substrates have shown fascinating electrocatalytic performance towards a wide range of electrochemical reactions and demonstrated great potential in practical applications. In this review, we summarize recent progress of 1D nanomaterial supported MSACs, from material synthesis, characterization, and theoretical calculation to their performance in five different kinds of electrochemical applications. In particular, the major synthetic strategies of these advanced MSACs and their catalytic performance and mechanisms in various electrocatalytic reactions are extensively discussed. Finally, the remaining challenges and future prospects of 1D nanomaterial supported MSACs are provided.